Globalization, Conflict and Security in Africa - Musa, Auwalu; Aide, Abdulrazak; Bayero, Abdullahi Ado; Shuaibu, Muawiya (Kashere Journal of Politics and International Relations, 2023)
Globalization has brought issues that are related to struggle for power and resources, identity contestation, border issues, religious fundamentalism, poverty, unemployment, exploitation and issues that are related to separatism/secession. These changes brought by globalization is changing the nature of conflicts and wars across Africa, from liberation struggle, to interstate, to intrastate and terrorism. This paper examined the globalization-Conflict synergy and their implications for security in Africa. It utilized qualitative and content analysis as methodology. The findings of the paper revealed that globalization operates like a double-edged sword in Africa, with both negative and positive impact on security. The negative impact of globalization in Africa is sophistication of conflict that has devastating effects on security and development. Globalization and conflict in that respect are two sides of a coin in Africa. The paper concluded that the implications of globalization in Africa are accompanied by multidimensional conflicts. This means that globalization has more negative than positive impact on security. Despite the fact that conflict is inevitable in human interactions, the nature of conflict influenced by globalization is intricate and precarious in its manifestations in Africa. The paper recommended among others that there is urgent needs to fight against corruption and deprivation; and has to be the top priority of most African leaders, because corruption can deprived many of their right and opportunity as citizens. Also, there is urgent need for solving the problem of unemployment as measure to curb security in most African states.